Coconut Plants (Cocos Nucifera L.) And Some Pests And Diseases That Attack Them - Yuza Defitri (Information Technology and Science (ITScience), 2025)
This study aims to identify several pests and diseases that attack coconut plants. The benefits of the plant lie not only in the flesh of the fruit, which can be processed into coconut milk, copra, and coconut oil, but all parts of the coconut plant have significant benefits. The method used for sampling was a purposive sampling method in the main nursery. In this study, sampling was conducted in one village with three nursery locations (f?, f?, and f?). The population at each nursery location was 130 seedlings. Therefore, the sample used was 15% of the 130 plants, namely 20 plants. The results of this study: coconut beetle pests can be controlled effectively with insecticides: Sevin 85 SP with a dose of 10 grams/tree where half is watered and the rest is sprinkled onto the shoots of the plant towards the growing point, with an interval of every two months - Lebaycid 50 EC, with a dose of 5 cc/liter of water/tree and an interval of two months - For preventive measures, Basudin 10 G can be used with a dose of 20 grams/tree directly sprinkled onto the shoots of the plant and repeated every 3 months.